COGNITIVE BEHAVIORAL THERAPY TO REDUCE DEPRESSION IN FEMALE COLLEGE STUDENTS FROM BROKEN HOMES - Yasintha Sari Pratiwi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to reduce depression levels among female college students from broken homes through the application of cognitive behavioral therapy. This study used a single-case experimental design. The subjects were selected using purposive sampling—three female college students from broken homes who were diagnosed with severe depression based on the Beck Depression Inventory (BDI-II). Data analysis in this study was conducted using data triangulation, which involved comparing increases or decreases in depression scores at the beginning and end of therapy sessions, supplemented by interviews and observations of the subjects regarding changes observed in each therapy session. The results indicate an improvement in the psychological condition of all three participants, marked by a reduction in depression levels from the severe category to the mild category. Qualitatively, positive changes were observed, characterized by the emergence of realistic thinking, more stable emotions, and more productive behavior. Based on these findings, it can be concluded that the application of cognitive-behavioral therapy can help reduce depression levels in female college students from broken homes